Política pública de incentivo à bovinocultura leiteira: o processo interdisciplinar de analisar o processo político de desenvolvimento em Marechal Cândido Rondon – PR - Neukirchen, Leandro César (2018)
The public policy processes developed in Brazil has a vital importance for the nation development and this is present in legislative measures and, in theory, in the executive branch actions. However, the market tends to privilege the large rural producers and when reflecting on this problem, we can observe the programs' inefficiency developed by the government for the small farmers. In addition, there is the problem of the contribution of society to the effectiveness of the public policies developed in Brazil, since this social cost aims to promote the activities development and the wealth distribution. Thus, this thesis aimed to analyze the public policy developed in the Marechal Cândido Rondon city, located in the western Paraná, which consists of distributing bovine semen to dairy cattle producers. This study used exploratory and descriptive research to compare municipal legislation with the results obtained by producers and public managers of this program. Also participating of this research professors from Western region public universities that had internship programs in milk production to verify how they evaluate this public policy. The results of the field research have confirmed the arguments that public policy diverges from the laws that created it. It was verified that the policy was effective in the beginning, but the change of public managers caused problems of availability, quality and control of semen distribution, making it inefficient. It was also observed that many actors involved in this policy naturalize their inefficiency and that there are differences about the milk production results, which points to the need for greater control of public managers. Therefore, this thesis points to the need to review the use of public resources in Marechal Cândido Rondon, as well as in Brazil, as this there are legal instruments that make it possible to reverse this situation.